AGRO-TECHNOLOGY FOR MAXIMIZING SEED SIZE TUBER YIELD - Rawal, Sanjay; Lal, S S.; Kumar, Parveen; Upadhayay, N. C (Potato Journal, 2013)
A field experiment was conducted at Modipuram, Meerut during 2002-04 in loamy soil will nine treatment combinations in randomized block design with four replications, consisting two intra-row spacings (10 & 15 cm) at a constant inter row spacing of 60 cm; two levels of N, P2O5 and K2O (100, 80-80 and 150-120-80 kg/ha) and two crop durations (70 and 80 days). A conventional control having 60 x 20 cm spacing, 150 kg N, 80 kg P2O5 and 100 kg K2O /ha and 75 days crop duration was kept for comparison. The seed size tubers of cultivar Kufri Sutlej were planted as per treatments in mid of October in both the seasons and rest package of practices recommended for seed crop in the region was followed. The crop emergence and shoot number/plant were not affected by any of the factors, while the maximum seed size tuber number was recorded with plant spacing of 10 cm, 100 kg N + 80 kg P2O5 + 80 kg K2O /ha (6,74,500 ha-1), significantly higher than other combinations, where as the lowest number was recorded with conventional control (3,86,800 ha-1). The similar trend was also observed for total tuber number/ha, where maximum number were recorded with plant spacing of 10 cm, 150 kg N + 120 kg P2O5 + 80 kg K2O /ha and 80 days duration and lowest in control. It may be concluded that the reduction of intra-row spacing to 10 cm may provide higher number of seed size tubers in comparison to other agronomic factors, like duration or increased macro-nutrient levels.